2018
DOI: 10.1556/066.2018.47.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of spray-drying process for concentrated orange juice

Abstract: Response surface methodology was used to optimize spray-drying process for concentrated orange juice. Independent variables were: inlet air temperature (130-170 ºC) and maltodextrin 12DE content (60-75% wet basis (wb)). Responses variables were powder yield, moisture, and ascorbic acid retention. Moisture content was negatively affected by inlet air temperature, while ascorbic acid retention was directly related. Powder yield and ascorbic acid retention increased with the rise in maltodextrin content, while mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 26 publications
3
9
2
Order By: Relevance
“…On the other hand, at high inlet air temperature, the extreme water loss caused the cracking of the particle membrane and induced a subsequent premature degradation of the encapsulated vitamin by the contact with air. This effect is in accordance with those reported in previous studies (Cuevas‐Glory et al, ; Pino et al, ). The temperature of the air cannot be so high that it causes thermal damage.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…On the other hand, at high inlet air temperature, the extreme water loss caused the cracking of the particle membrane and induced a subsequent premature degradation of the encapsulated vitamin by the contact with air. This effect is in accordance with those reported in previous studies (Cuevas‐Glory et al, ; Pino et al, ). The temperature of the air cannot be so high that it causes thermal damage.…”
Section: Resultssupporting
confidence: 94%
“…Table showed that the ascorbic acid retention ranges from 73.3 to 89.9%, representing that the difference between the maximum and minimum value of ascorbic acid retention was 16.6%, which is due to the high sensitivity of this vitamin to high temperatures. These results were close to the 79.5% found for the spray drying of guava pulp (Chopda & Barrett, ) and 66.7–80.5% (Patil et al, ), as well as of other fruit juices dried by the same technique (Islam et al, ; Cuevas‐Glory et al, ; Pino et al, ).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations